2006
DOI: 10.5194/npg-13-125-2006
|View full text |Cite
|
Sign up to set email alerts
|

Energy-conserving and Hamiltonian low-order models in geophysical fluid dynamics

Abstract: Abstract. Arbitrary truncations in the Galerkin method commonly used to derive low-order models (LOMs) may violate fundamental conservation properties of the original equations, causing unphysical behaviors in LOMs such as unbounded solutions. To avoid these, energy-conserving LOMs are developed in the form of coupled Volterra gyrostats, based on analogies between fluid dynamics and rigid body mechanics. Coupled gyrostats prove helpful in retaining in LOMs the Hamiltonian structure of the original equations. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…Like the former, the latter problem may also be difficult since linear models are inappropriate, whereas the multitude of nonlinear models is overwhelming. As way to handle the problem, one might consider physically sound low-order models that possess fundamental properties of fluid dynamical equations (in the spirit of Lorenz, 1963, 1982and Obukhov, 1973, see also Gluhovsky, 2006), thereby infusing more physics into time series analysis. From the perspective of complexity theory, the development of appropriate statistical methods for atmospheric and climate data analysis should be based on time series spawned by the underlying dynamics rather than on traditional time series models (cf., Nicolis and Nicolis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Like the former, the latter problem may also be difficult since linear models are inappropriate, whereas the multitude of nonlinear models is overwhelming. As way to handle the problem, one might consider physically sound low-order models that possess fundamental properties of fluid dynamical equations (in the spirit of Lorenz, 1963, 1982and Obukhov, 1973, see also Gluhovsky, 2006), thereby infusing more physics into time series analysis. From the perspective of complexity theory, the development of appropriate statistical methods for atmospheric and climate data analysis should be based on time series spawned by the underlying dynamics rather than on traditional time series models (cf., Nicolis and Nicolis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a LOM for the magnetohydrodynamics of a toroidal confinement device (Chen et al, 1990) can easily be shown to have the form of a gyrostat with three nonlinear terms and one pair of linear terms. It is also notable that Hamiltonian LOMs based on gyrostats inherit the Hamiltonian structure (hence all conservation properties) of the original equations (Gluhovsky, 2006). These examples provide further evidence that coupled gyrostats can be employed in a physically motivated, modular approach to designing LOMs based on spectral Galerkin approximations.…”
Section: Discussionmentioning
confidence: 84%
“…A physicallymotivated, modular approach to designing LOMs using the Galerkin method has been introduced (Gluhovsky, 1982(Gluhovsky, , 1986Gluhovsky and Tong, 1999;Gluhovsky et al, 2002;Gluhovsky, 2006). This approach is based on designing LOMs so that their mathematical equations have a structure isomorphic to those for systems known in mechanics as coupled gyrostats, with friction and forcing.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of energy conservation was solved in [50] where a universal criterion for the truncation to energy-conserving finite-mode models was established. Moreover, truncation to systems in coupled gyrostats form [18,19] may also lead to models that retain the conservation properties of the original equations. We also note, that a single gyrostat is a Nambu system and hence using such a truncation, conservation of the underlying geometry may be implemented at least in some minimal form.…”
Section: Maximum Simplificationmentioning
confidence: 99%